Las estrategias de modelado para el desarrollo de la grafomotricidad en los niños de cuatro y cinco años de la escuela República de Chile, provincia de Chimborazo, cantón Colta, parroquia Columbe, durante el año lectivo 2014 – 2015 - Valente Balla, Dina Judith (2016)
This research was conducted in the República de Chile School since modeling strategies is a very important issue and even more relating to the development of the graph motor; because the child acquires the necessary skills and comes to express through written signs, through exercises that allow greater control of the forearm, wrist, hand and above all fingers. Within the methodology applied and framed within the objectives activities that will help to develop graph motor were identified. The research was developed with a population of 39 children from 4 to 5 years of this school, the research method used was inductive, deductive and analytical, in order to understand and analyze this reality. The type of the implemented research was explanatory and bibliographic documentary and field; also to data collection the observation technique was used. After the diagnosis some findings were identified and it was shown that the highest percentage of children have difficulty in the development of imagination, fantasy and creativity. A Guide modeling strategies as a working tool is made. In conclusion of this shortcomings in the implementation of strategies and modeling work by manipulating sponges, chalk, thick brushes and waxes were identified, which directly affects the physical, intellectual, perception and visual training affecting directly the perfection of movements of hands and fingers in children. It is suggested implementing a strategy guide of modeling because this is the first process of written language acquisition, it will also allow the child to acquire the necessary skills to reach expression allowing the development of graph motor in children of four and five years of the República de Chille School.